Kalin Yanakiev as a Writer of Apocrypha? Remarks on the Essay "Дебат върху теодицеята" ("A Debate on Theodicy") - Szwat-Gyłybowa, Grażyna; Szymczak, Piotr (Studia Ceranea, 2014)
The article engages with the philosophical and theological notion of theodicy as formulated by Kalin Yanakiev in Дебат върху теодицеята (A Debate on Theodicy), an essay which appeared in Yanakiev’s book Философски опити върху самотата и надеждата (Philosophical Essays on Solitude and Hope,2008). The article uses the category of apocryphalness to analyse the ideas sparked off in Yanakiev’s work by a passage from Dostoevsky’s The Brothers Karamazov, along with a series of Yanakiev’ s philosophical and poetic images which are interpreted in the biblical and philosophical context. The article also touches on the relationships between Yanakiev’s ideas and Orthodox Christian theodicy.